2009
DOI: 10.1094/cchem-86-5-0549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Temperature for Paddy on Consumer Perception of Cooked Rice

Abstract: Effect of storage temperature (ST) (5, 15, and 25°C) for paddy on the consumer perception of cooked rice (CR) was investigated with six major rice cultivars in Korea (Ilmibyeo, Chucheongbyeo, Ilpumbyeo, Hwayeongbyeo, Nampyeongbyeo, and Odaebyeo) after 12 months of storage. Germination rate (GR) of the paddy, grading characteristics (percentages of head rice, broken kernels, damaged kernels, colored kernels and chalky kernels) of milled rice (MR) kernels, texture profile analysis (hardness, springiness, cohesiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Ageing during storage leads to numerous changes in the chemical and physical properties of rice (Noomhorm et al, 1997;Perdon et al, 1999;Pearce et al, 1999;Suzuki et al, 1999;Sowbhagya & Bhattacharya, 2001;Zhou et al, 2002;Sodhi et al, 2003;Patindol et al, 2005;Singh et al, 2006;Cao et al, 2009). These changes in rice pasting properties, color, flavor, and composition result in rice cooking and eating quality (Meullenet al, 2000;Teo et al, 2000;Jang et al, 2009) and depend on the rice variety, storage conditions, and amylose content. Such changes have been attributed to changes in cell walls and proteins, interaction between proteins and the degradative products of lipid oxidation, and starch-protein interaction (Sodhi et al, 2003;Park et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ageing during storage leads to numerous changes in the chemical and physical properties of rice (Noomhorm et al, 1997;Perdon et al, 1999;Pearce et al, 1999;Suzuki et al, 1999;Sowbhagya & Bhattacharya, 2001;Zhou et al, 2002;Sodhi et al, 2003;Patindol et al, 2005;Singh et al, 2006;Cao et al, 2009). These changes in rice pasting properties, color, flavor, and composition result in rice cooking and eating quality (Meullenet al, 2000;Teo et al, 2000;Jang et al, 2009) and depend on the rice variety, storage conditions, and amylose content. Such changes have been attributed to changes in cell walls and proteins, interaction between proteins and the degradative products of lipid oxidation, and starch-protein interaction (Sodhi et al, 2003;Park et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that consumer perception of domestic rice versus foreign rice is needed to prepare for liberalization of rice market in Korea, currently no information is available. Most rice research has focused on its physicochemical characteristics and the sensory attributes that affect consumer acceptance of cooked rice 15–19. For example, Suwansri and Meullenet15 evaluated the physicochemical properties and the acceptance of 15 rice samples (three commercially US grown and 12 imported jasmine rice samples) by 105 Asian families in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al 4 reported that storage temperature is a major factor affecting the colour of milled rice, with the value of b * increasing as storage temperature increased. Lee et al 5 showed an increase in b * of cooked rice as storage time of rough or milled rice increased from 1 to 3 years at 4 °C.…”
Section: Introductionmentioning
confidence: 99%